2023
DOI: 10.1038/s41591-023-02240-8
|View full text |Cite
|
Sign up to set email alerts
|

Codon-specific KRAS mutations predict survival benefit of trifluridine/tipiracil in metastatic colorectal cancer

Abstract: Genomics has greatly improved how patients with cancer are being treated; however, clinical-grade genomic biomarkers for chemotherapies are currently lacking. Using whole-genome analysis of 37 patients with metastatic colorectal cancer (mCRC) treated with the chemotherapy trifluridine/tipiracil (FTD/TPI), we identified KRAS codon G12 (KRASG12) mutations as a potential biomarker of resistance. Next, we collected real-world data of 960 patients with mCRC receiving FTD/TPI and validated that KRASG12 mutations wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…Despite the rapid progress in the development of innovative cancer therapy modalities in recent years, chemotherapy and radiotherapy are still the most extensively applied cancer treatment methods in the clinic nowadays. In the meanwhile, owing to the increasing understanding in the area of immune-oncology, it is now well recognized that tumor immunity could be affected by existing cancer therapies and would in turn determine their final therapeutic responses . For instance, the tumor microenvironment (TME) may be altered during chemotherapy or radiotherapy, and the immunosuppressive TME would largely protect tumor cells from immune attacks and limit the efficacies of those treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the rapid progress in the development of innovative cancer therapy modalities in recent years, chemotherapy and radiotherapy are still the most extensively applied cancer treatment methods in the clinic nowadays. In the meanwhile, owing to the increasing understanding in the area of immune-oncology, it is now well recognized that tumor immunity could be affected by existing cancer therapies and would in turn determine their final therapeutic responses . For instance, the tumor microenvironment (TME) may be altered during chemotherapy or radiotherapy, and the immunosuppressive TME would largely protect tumor cells from immune attacks and limit the efficacies of those treatment .…”
Section: Introductionmentioning
confidence: 99%
“…39 The latest discovery TherapeuTic advances in chronic disease suggests that codon-specific KRAS mutations can predict survival benefit of TAS-102. 40 In our study, we found that the benefits from front-line therapy was an independent indicator for PFS of third-line therapy. The similar results were reported in another chemotherapy rechallenge study from Turkey.…”
Section: Discussionmentioning
confidence: 48%
“…The results of a meta-analysis suggest maintained efficacy regardless of the mutation in codon 12 or 13 [27]; however, the presence of a KRAS codon 12 mutation was associated with lesser OS benefit of TTP relative to placebo unlike the mutation in codon 13 which did not reduce the OS benefit. Furthermore, a more recent study that included patients treated in a real-world setting, as well as patients from RECOURSE, showed the KRAS G12 mutations may be considered biomarkers for reduced OS benefit of TTP treatment [28].…”
Section: Discussionmentioning
confidence: 99%